Oak Biomass in the Form of Wood, Bark, Brushwood, Leaves and Acorns in the Production Process of Multifunctional Biochar - Bogdan Saletnik; Aneta Saletnik; Grzegorz Zaguła; Marcin Bajcar; Czesław Puchalski (Molecules, 2022)
Biochar from forest biomass and its remains has become an essential material for environmental engineering, and is used in the environment to restore or improve soil function and its fertility, where it changes the chemical, physical and biological processes. The article presents the research results on the opportunity to use the pyrolysis process to receive multifunctional biochar materials from oak biomass. It was found that biochars obtained from oak biomass at 450 and 500 °C for 10 min were rich in macronutrients. The greatest variety of the examined elements was characterized by oak-leaf pyrolysate, and high levels of Ca, Fe, K, Mg, P, S, Na were noticed. Pyrolysates from acorns were high in Fe, K, P and S. Oak bark biochars were rich in Ca, Fe, S and contained nitrogen. In addition, biomass pyrolysis has been found to improve energy parameters and does not increase the dust explosion hazard class. The oak biomass pyrolytic at 450 and 500 °C after 10 min increases its caloric content for all samples tested by at least 50%. The highest caloric value among the raw biomass tested was observed in oak bark: 19.93 MJ kg−1 and oak branches: 19.23 MJ kg−1. The mean and highest recorded Kstmax were 94.75 and 94.85 bar s−1, respectively. It can be concluded that pyrolysis has the potential to add value to regionally available oak biomass. The results described in this work provide a basis for subsequent, detailed research to obtain desired knowledge about the selection of the composition, purpose, and safety rules of production, storage, transport and use of biochar materials.